WACANA HIPERREALITAS DALAM FILM BERGENRE FANTASI - Arwin Purnama Jati (DeKaVe, 2013)
Global culture and industrial society have been raise production and consumption habits. Thediscourse is related to the role of media as a culture-mass product. Film with fantasy genre is part ofculture-mass product which has influenced the society significantly. Media is formed by narration andvisual signs which creates social habits pattern. Fantasy films as itself reconstruct the audience's mind,accommodate idea and imagination oflife and its social relations.As it is formed in mind of the audience, imagination represents the need of "new-world" realitiesthat is virtual means, which is produced as a consequence of digital revolution and technology productthat are both related to the necessity of production. In this case, there is continuity production of visualsigns, therefore treats to the rise of"hiperreality" by its product, that isfantasy:film as a discourse.Keywords: Hyperreality, Film, Virtual, Fantasy